THE USE OF GUESSING GAME TO IMPROVE STUDENT’S SPEAKING SKILL - Sri Wahyuni; Fitri Yulianti (Getsempena English Education Journal, 2016)
Speaking is activity of two or more people in sending and receiving information or messages in oral communication. The reason for teaching speaking to students is because it belongs to the basic language skill in English. In speaking classes, the teacher usually give a dialogue of a certain topic, then the students are being to practice and memorize the dialogue with their friends and finally present the dialogue in front of the class in turn. It means that to understand the dialogue, the students must have the ability in vocabulary, grammar and pronunciation. Because of that, speaking is very important to be taught to the students.This study aimed to find out whether the use of guessing game is effective. The sample of the study consist of 27 students in one class. The data in this research were conducted by using pre-test and post-test. The result from the research showed that there is significant difference between the students who are taught speaking by using guessing game and those who are taught speaking by using traditional approach. The finding indicated that there is a significant difference between the score of pre-test was 53, 6 and post-test was 82, 9. From this research it was known that t – score is highest than t – table. It’s mean that this alternative hypothesis (Ha) is accepted. Thus clear that the difference of the two means gained score was significant.